2009
DOI: 10.1038/bmt.2009.152
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients with diffuse large B-cell non-Hodgkin's lymphoma receiving purged autografts after induction failure

Abstract: Patients with diffuse large B-cell lymphoma (DLBCL) who do not achieve a complete response to front-line combination chemotherapy are often offered high-dose therapy and autologous hematopoietic cell transplantation (AHCT). However, the efficacy of this therapy in this patient population has been addressed in only a few published reports. We retrospectively analyzed the outcomes of patients with a diagnosis of de novo DLBCL who underwent AHCT at our center between 1988 and 2002, and identified 43 consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…As expected ([38] and literature therein), dynamic parameters, such as response to therapy and especially failure to achieve complete remission, which are not obtainable at diagnosis, seem to be the most reliable outcome indicators in DLBCL, yet expression of CD5 and FOXP1 added information independent of these disease dynamic parameters.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As expected ([38] and literature therein), dynamic parameters, such as response to therapy and especially failure to achieve complete remission, which are not obtainable at diagnosis, seem to be the most reliable outcome indicators in DLBCL, yet expression of CD5 and FOXP1 added information independent of these disease dynamic parameters.…”
Section: Discussionsupporting
confidence: 74%
“…Within this prospective study, we identified potential biomarkers (expression of CD5 for EFS and expression of FOXP1 for OS) that were able to predict the course of DLBCL at diagnosis, independent of stage and IPI. As expected ([ 38 ] and literature therein), dynamic parameters, such as response to therapy and especially failure to achieve complete remission, which are not obtainable at diagnosis, seem to be the most reliable outcome indicators in DLBCL, yet expression of CD5 and FOXP1 added information independent of these disease dynamic parameters.…”
Section: Discussionsupporting
confidence: 74%